Implementation of the WTO Agreement on Customs Valuation in Vietnam : Trade Integration and Local Compliance at Da Nang Port - Le, Doan Hong; Nayyar, Anand; Rots, Nhung Le (Indian Journal of Finance, 2018)
WTO customs valuation under the Customs Valuation Agreement (CVA) contained in GATT 1994 is very recent in Vietnam and is now getting more detailed scrutiny and implementations via revised procedures and regulations. The Customs Valuation Agreement lays strong foundation for enhancing global trade relations. Vietnam implemented the WTO Customs Valuation Agreement through the 2007 Customs Law and related regulations, which improvised the customs valuation process. Apart from being highly positive, U.S. exporters cited various issues with regard to its inefficiency, unclear policies, and corruption. The objective of this research paper was to provide a detailed overview of the impact of the Customs Valuation Agreement (CVA) on trade policy in Vietnam and to evaluate the impact of CVA on trade integration. In this research paper, we presented a detailed analysis of the study conducted at the Port of Da Nang to evaluate the Customs Valuation Agreement. The study conducted proved that the CVA policy still has certain limitations and requires revisions. The paper also recommended certain points regarding improvements towards the CVA policy to make it preferable towards international trading in Vietnam.